2014
DOI: 10.1097/qad.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

The role of mathematical modelling in the development of recommendations in the 2013 WHO consolidated antiretroviral therapy guidelines

Abstract: Despite the exponential growth in the literature on modelling and simulation studies of impact and cost-effectiveness in different aspects of healthcare, there is no clear consensus on the appropriate role of modelling in the development of recommendations in clinical guidelines. This is compounded both by the lack of a standardised approach to assess the quality of modelling, and lack of clarity on its positioning within the GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The quality management techniques collectively known as "Six Sigma" have been practiced in health care for several decades, and for even longer in manufacturing, business, and industry (3,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The implementation of Sigma metrics has mostly occurred in laboratory subspecialties, such as chemistry, hematology, and immunology.…”
Section: A "Traditional" Approach To Quality: Six Sigmamentioning
confidence: 99%
“…The quality management techniques collectively known as "Six Sigma" have been practiced in health care for several decades, and for even longer in manufacturing, business, and industry (3,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The implementation of Sigma metrics has mostly occurred in laboratory subspecialties, such as chemistry, hematology, and immunology.…”
Section: A "Traditional" Approach To Quality: Six Sigmamentioning
confidence: 99%
“…A final paper, from the WHO staff [14], considers the use of modeling from the point of view of the guideline setting body and describes where models could help the process, as well as how modeling could more constructively contribute to policy formulation in the future. A key point raised is that factors beyond the costeffectiveness recommendations from models will be considered when taking policy decisions.…”
Section: S2mentioning
confidence: 99%
“…Mathematical models are increasingly used to aid decision making in public health and clinical medicine . The results of mathematical modeling studies can provide evidence when a systematic review of primary studies does not identify sufficient studies to draw conclusions or to support a recommendation in a guideline, or when the studies that are identified do not apply to the specific populations of interest or do not provide data on long‐term follow‐up or on relevant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models are increasingly used to aid decision making in public health and clinical medicine. 1,2 The results of mathematical modeling studies can provide evidence when a systematic review of primary studies does not identify sufficient studies to draw conclusions or to support a recommendation in a guideline, or when the studies that are identified do not apply to the specific populations of interest or do not provide data on longterm follow-up or on relevant outcomes. For example, mathematical models have been used to inform guideline recommendations about tuberculosis (TB) control in health care facilities, 3 blood donor suitability with regard to human T-cell leukemia virus type I (HTLV-I) infection, 4 and cancer screening.…”
Section: Introductionmentioning
confidence: 99%